Growth in children aged 5 to 15 years with special reference to sexual maturity rating: cross-sectional study - Cherian, Carol Sara; Sajan, Bibin (International Journal of Contemporary Pediatrics, 2022)
Background: Puberty is a critical period for children since hormonal changes impact directly on linear and sexual growth. This study aimed to assess the growth pattern of children aged 5-15 years with special reference to sexual maturity and to find association of sexual maturity rating (SMR) with body mass index (BMI) and socioeconomic scores. Methods: Cross sectional study was done in Pushpagiri Institute of Medical Sciences a tertiary care hospital. The 910 children in the age group of 5 to 15 years with consent /assent formed the study group via multistage sampling. Study period was for 18 months (March 2016 to September 2017). Physical examination included anthropometry and SMR by Tanner staging. Probit analysis was done to calculate the mean ages of attainment of SMR. Bivariate analysis and Pearson’s chi-square test were used to test the possible association between SMR and BMI/ socioeconomic status. Results:910 children were included in the study (M:F=1.25:1). The mean and 50th percentile values for height and weight were in close agreement in all age groups in both sexes. The maximum increase in height was noted between 11-12 years in girls and 14-15 years in boys. The mean age of onset of Gonadarche and Pubarche in boys was 11.4±0.99 years and 12.4±1.36 years respectively. The mean age of attainment of Thelarche, pubarche, and menarche was 10.4±1.38, 10.9±1.29, and 11.2±1.56 years respectively in girls. The time interval between Thelarche and Menarche was 10 months. The association of thelarche with SES was statistically significant (p<0.001). Overweight/obese girls showed 9.6 months earlier onset of thelarche when compared to the normal/thin subjects. Conclusions: The study yielded normative values for height, weight, and sexual maturation patterns in children of central Kerala. Obese/overweight female subjects tend to attain sexual maturation earlier compared to non-obese subjects.